Epithelial and macrophage cell interaction in cervical cancer through single-cell RNA-sequencing and spatial analysis - Wang, Zhichao; Cheng, Long; Li, Guanghui; Cheng, Huiyan (Frontiers in Immunology, 2025)
BackgroundCervical cancer (CC) is a major global health issue, ranking sixth in cancer-related mortality. The tumor microenvironment (TME) plays a crucial role in tumor growth. This study explored the cellular composition and immunological landscape of CC using various genomic data sources.MethodsData from the Cancer Genome Atlas and Gene Expression Omnibus were analyzed, including single-cell RNA sequencing, spatial transcriptome analysis, and survival data. Gene set variation analysis (GSVA) identified pathways in CD8+ cells, macrophages, and epithelial cells. Immunohistochemistry assessed marker expression in CC and normal tissues. Tumor immune dysfunction and exclusion (TIDE) scores differentiated high- and low-macrophage groups. Cell–cell communication analyses highlighted interactions between macrophages and epithelial cells.ResultsMacrophage markers correlated with overall survival (OS) and disease-free survival (DFS). Epithelial cell subgroups 1 and 4, along with CD8+ T cells, were associated with OS. TIDE scores varied between groups. Specific ligand-receptor interactions were found between macrophages and epithelial cell subgroup 1. Triptolide was effective in epithelial cell subgroup 1, while memantine was more effective in macrophages.ConclusionEpithelial-macrophage interactions in the TME are crucial for CC progression and treatment, offering a potential immunotherapeutic strategy.